Analysis of Tiktok-Based Learning Media from the Perspective of Progressivism Educational Philosophy - Nabilah, Shabrina; Abidah, Dewi; Simanjuntak, Nensy Megawati (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to evaluate the use of TikTok as a learning medium in the context of progressivism philosophy. A qualitative research method with a literature review approach was employed to gather data from various academic sources. The findings indicate that TikTok can enhance students' understanding through engaging and interactive video content, aligning with progressivism principles that support the use of technology in education. Despite some drawbacks, such as the potential for excessive use, TikTok has proven effective in motivating students and making learning more engaging. In conclusion, integrating TikTok in learning aligns with progressivism principles that encourage innovation and technological adaptation to achieve better education.